Effectiveness of Android-Based Learning Media “Teman Ritma” to Improve Problem-Solving Skills of SMP Negeri 5 Yogyakarta - Ardhika Fajar Ramadhan; Nuryadi Nuryadi; Muhammad Faisal (Universitas Mercu Buana Yogyakarta, 2022)
Problem-solving is an essential ability that must be achieved by each individual and problem-solving itself has become integral part of mathematics learning. However, many Indonesian students need problem-solving skills. Android-based learning media is one of the efforts in improving students' problem-solving skills. This study aims to find out the effectiveness of the use of android-based learning media called Teman Ritma. This research is kind of experimental research in the form of true-experimental with a design namely pretest post-test control group design. The sample is determined using purposive sampling techniques and produces a sample i.e., class VII-G students as a control group and class VII-H students as an experimental group with the number of students from each group is 30 students. Data collection techniques use observations, interviews, pretest questions and post-test problem-solving skills that contain social arithmetic material. The results showed that the use of android based learning media “Teman Ritma” was effective in improving students' problem-solving skills. This statement is proved by the results of the Mann-Whitney test which shows that Asymp's value. Sig. (2-tailed) less than 0.05 (0.027 0.05) which means that learning with Teman Ritma media is more effective than using the learning media that teachers use. This conclusion was reinforced based on an average difference test that showed that the average increase in the experimental group was higher than that of the control group (60.12 45). Based on the test, it concluded that the use of android-based learning media “Teman Ritma” is effective to improve the problem-solving skills of seventh-grade students of SMP Negeri 5 Yogyakarta.